PENGARUH METODE MONTESSORI TERHADAP PEMAHAMAN BERBAHASA INDONESIA DI SEKOLAH SRI AMAN SUKSA SCHOOL SATUN THAILAND - Syahlita, Elvina; Amelia , Chairunnisa; Nasution , Dewi Kesuma (Jurnal Pendidikan Dasar, 2023)
The Montessori method is a method formulated based on Montessori theory which can be used in the realm of children's education and is structured based on theories about child development. The most visible characteristic of this method is that it emphasizes the activities generated by the child by emphasizing the process of adapting to the child's learning environment which is shaped according to the stage of development, using the role of physical activity in absorbing learning concepts to have practical abilities. This article aims to describe the influence of the Montessori method on understanding Indonesian at Sri Aman Suksa School Satun Thailand. The research method used in this research is descriptive quantitative, namely in the form of active participant observation and documentation, which is a data collection technique that the author uses as an effort to collect information at Sri Aman Suksa School Satun Thailand. The results of research related to the application of the Montessori method using stimulus activities in accordance with Maria Montessori principles, it turns out that learning can improve students' understanding of Indonesian at Sri Aman Suksa School Satun Thailand.